2021
DOI: 10.1038/s41467-021-27452-9
|View full text |Cite
|
Sign up to set email alerts
|

A targetable LIFR−NF-κB−LCN2 axis controls liver tumorigenesis and vulnerability to ferroptosis

Abstract: The growing knowledge of ferroptosis has suggested the role and therapeutic potential of ferroptosis in cancer, but has not been translated into effective therapy. Liver cancer, primarily hepatocellular carcinoma (HCC), is highly lethal with limited treatment options. LIFR is frequently downregulated in HCC. Here, by studying hepatocyte-specific and inducible Lifr-knockout mice, we show that loss of Lifr promotes liver tumorigenesis and confers resistance to drug-induced ferroptosis. Mechanistically, loss of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 85 publications
(108 reference statements)
4
114
0
Order By: Relevance
“…It should be noted that a recent study found that sorafenib was not a bona fide inducer of ferroptosis based on screening results using a panel of cancer cell lines [ 98 ]. Another recent study found that LIFR (leukemia inhibitory factor receptor) sensitized HCC cell lines to sorafenib-induced ferroptosis both in vitro and in vivo, whereas loss of LIFR expression confers resistance to sorafenib-induced ferroptosis [ 99 ]. These contradictory results might be attributed to different cellular contexts such as the expression levels of LIFR and/or other undefined genes/pathways related to the sensitivity of sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that a recent study found that sorafenib was not a bona fide inducer of ferroptosis based on screening results using a panel of cancer cell lines [ 98 ]. Another recent study found that LIFR (leukemia inhibitory factor receptor) sensitized HCC cell lines to sorafenib-induced ferroptosis both in vitro and in vivo, whereas loss of LIFR expression confers resistance to sorafenib-induced ferroptosis [ 99 ]. These contradictory results might be attributed to different cellular contexts such as the expression levels of LIFR and/or other undefined genes/pathways related to the sensitivity of sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is well-known to be a malignant cancer and highly effective therapeutic drugs or approaches are insufficiency [ 1 , 2 ]. Of note, Solanum nigrum L .…”
mentioning
confidence: 99%
“…The way in which to sensitize therapy-resistant cancer cells to ferroptosis remains one of the most important questions that needs to be addressed. Very recently, Yao et al showed that the loss of the tumor suppressor gene encoding leukemia inhibitory factor receptor (LIFR) confers resistance to ferroptosis-inducing drugs through upregulation of iron-sequestering cytokine lipocalin-2 (LCN2) [240]. Therefore, anti-LCN2 therapy using LCN2-neutralizing antibody could be used in combination with sorafenib to improve liver cancer treatment by targeting ferroptosis.…”
Section: Clinical Trials In Hcc Treatmentmentioning
confidence: 99%
“…Therefore, anti-LCN2 therapy using LCN2-neutralizing antibody could be used in combination with sorafenib to improve liver cancer treatment by targeting ferroptosis. Additionally, there are hints that this may have the potential to sensitize tumors to radiation, which requires further investigation [240].…”
Section: Clinical Trials In Hcc Treatmentmentioning
confidence: 99%
See 1 more Smart Citation